Sulfur Betaines from S-Propargyl Xanthates. Unusual Chemistry from a Simple Functional Group - Zard, Samir Z. (Synthesis, 2019)
S-Propargyl xanthates undergo upon heating a [3,3] sigmatropic rearrangement followed by a reversible ring closure into a novel betaine. This betaine can be implicated in carbon–carbon bond forming processes, in the synthesis of esters, in the inversion of secondary alcohols, in the formation of alkenes, for the generation of rigid, cisoid dienes that are highly reactive in both inter- and intra-molecular Diels–Alder cycloadditions, and in various other synthetically useful transformations.1 Introduction2 An Unexpected Transformation3 Evidence for the Betaine Intermediate4 A Method for the Synthesis of Esters and for the Inversion of Secondary Alcohols5 A General Alkylation Process6 The Case of Carbon Acids7 A Synthesis of Alkenes8 Further Trapping Experiments. Concerted or Not Concerted?9 Rigid Cisoid Dienes10 Propargyl Radicals11 Concluding Remarks
Keywords: S-propargyl xanthates; sigmatropic rearrangement; betaines; esters; inversion; cycloaddition